Pengaruh Audit Internal dan Efektivitas Pengendalian Internal Terhadap Pencegahan Kecurangan (Fraud) Pada Bank Bumn di Denpasar - Komang Yoga Mahendra; A.A.A Erna Trisna Dewi; Gst Ayu Intan Saputra Rini (Jurnal Riset Akuntansi Warmadewa, 2021)
This study aim to see how the influence of internal audit and internal control on fraud prevention at state-owned banks in Denpasar. The method of data analysis was carried out by means of a questionnaire to all bank employees who were respondents as many as 80 people. The data analysis technique used is multiple linear regression analysis F test, t statistical test, coefficient of determination (R2) and classical assumptions consisting of normality test, multicollinearity test, and hetero cedasticity test. Based on the results of the t statistical hypothesis test, it explains that internal audit has a positive effect on fraud prevention at BUMN Banks in Denpasar, the authorities have a positive effect on fraud prevention at BUMN Banks in Denpasar. Based on the results of the F hypothesis test, it explains that the internal audit variable has a positive and significant effect on the fraud prevention variable at BUMN Banks in Denpasar.